Long-term relaxation of photoconductivity in cadmium doped Gd₂S₃ films - Jabua, Z.U.; Gigineishvili, A.V.; Tabatadze, I.G.; Kupreishvili, I.L. (Физическая инженерия поверхности, 2011)
In first time it is experimentally investigated some regularities of long-term relaxation of photoconductivity of gadolinium one-and-halp sulfides thin films doped by cadmium atoms. Was calculated maximum of recombination barrier and found the location of trapping levels in the gap. Вперше експериментально досліджені деякі закономірності довгострокової релаксації фотопровідності плівок полуторного сульфіду гадолінія, які леговані атомами кадмію. Розраховано максимальне значення рекомбінаційного бар’єру та встановлено розташування рівнів прилипання в забороненій зоні. Впервые экспериментально исследованы некоторые закономерности долговременной релаксации фотопроводимости плёнок полуторного сульфида гадолиния, легированных атомами кадмия. Рассчитано максимальное значение рекомбинационного барьера и установлено расположение уровней прилипания в запрещённой зоне.